HyperXpress: Rapid Single Vessel DNA Assembly and Protein Production in Microliterscale - Zibulski, Darius Leon; Schlichting, Niels; Kabisch, Johannes (Frontiers in Bioengineering and Biotechnology, 2022)
Rapid prototyping of biological functions has the common aim of generating, screening, and selecting variant libraries as quickly as possible. This approach is now to be extended by the HyperXpress workflow, which connects ligase cycling reaction for DNA assembly, multiply-primed rolling circle amplification for signal amplification, and cell-free protein synthesis to a single vessel reaction in the lower µl scale. After substantial optimization of the method a proof-of-principle demonstrating the high flexibility of HyperXpress for semi-rational protein engineering by expanding, reducing, and replacing β-strands of three different green fluorescent proteins is described. These single-day experiments resulted in six functional, new-to-nature GFP prototypes.